Prostaglandin E2 promotes BeWo spheroids implantation in RL95-2 cell monolayers. (3rd July 2017) - Huang, Xiaman; Liu, Haizhi; Li, Ruiman
Abstract: Purpose : Integrin αvβ3 (ITG αvβ3) participates in the process of implantation between the embryo and the endometrium. This study investigated the effects of prostaglandin E2 (PGE2 ) on endometrial receptivity and implantation efficiency of the embryo, and their possible mechanisms. Methods : Quantitative real-time reverse transcription PCR (qRT-PCR) and western blotting were used to detect the changes in mRNA and protein levels of ITG αvβ3 in RL95-2 cells after administering PGE2 . BeWo trophoblast cells and RL95-2 endometrial epithelial cells were used to establish an in vitro model, which was used to observe the adhesion rate and spreading efficiency between BeWo spheroids and RL95-2 cell monolayers after pretreatment with different concentrations of PGE2 . Results : PGE2 at 200 nM increased the mRNA and protein levels of ITG αv significantly ( p  < 0.05); 100 nM PGE2 increased the mRNA and protein levels of ITG β3 significantly ( p  < 0.05). PGE2 at 200 nM increased significantly the adhesion and spreading efficiency of BeWo spheres to RL95-2 cell monolayers. Conclusions : An appropriate concentration of PGE2 might increase the expression of ITG αvβ3, which would, promote embryo adhesion and spreading efficiency. This study provides further evidence that increased expression of ITG αvβ3 might promote implantation by improving endometrial receptivity.